Hubungan Dukungan Sosial dengan Motivasi ibu dalam Memberikan ASI pada Bayi Berat Lahir Rendah (BBLR) - Susanti Widiastuti; Yeni Rustina; Nur Agustini (Akademi Keperawatan RSPAD Gatot Soebroto, 2019)
Breast milk (breast milk) has been known for many benefits, but breastfeeding is still a problem. The purpose of this study was to identify social support and motivation in breastfeeding. The design of this study is descriptive analysis using cross sectional or cross sectional approach. Sampling technique with non probability sampling with the type of purposive sampling with a sample of 43 respondents. The results showed there was a relationship of social support with the mother's motivation in giving breast milk to LBW (p